PENGARUH PEMBERIAN SEDIAAN CURCUMA DALAM SUSU DAN EMULSI TERHADAP PARAMETER FARMAKOKINETIKA PARASETAMOL - Kusuma, Anjar Mahardian; Rahayu, Wiranti Sri; Maryati, Siti; Sobarani, Rini Afini (Universitas Ahmad Dahlan, 2013)
ine